The impact of age-friendly communities on the quality of life of older adults based on structural equation modeling - Tang, Ying; Xu, Jie; Yu, Jingyu (Frontiers in Public Health, 2025)
BackgroundWith the aging of China’s population deepening, the development of age-friendly communities (AFCs) is playing an important role in alleviating the pressure of older adult care and enhancing the quality of life (QoL) of older adults. This paper aims to investigate the complicated impact of AFCs on the QoL of older adults through a questionnaire survey.MethodsA questionnaire survey was designed to explore the intricate relationships between components of AFCs and QoL factors from older adults’ perspective. A total of 1,396 older adults completed the survey. Factor analysis was used to identify AFC components and QoL factors, and the relationships between AFC components and QoL factors were predicted using structural equation modeling (SEM).ResultsFour AFC components and three QoL factors for older adults were identified. The SEM results revealed that (1) physical health was mainly positively influenced by green spaces and negatively affected by public healthcare services; (2) apart from public transportation, most AFC components were indicative of psychological health; and (3) social networks were primarily influenced by green spaces and community support.ConclusionTo provide a better living environment for older adults, it is suggested that communities renovate existing structures to expand green spaces, add accessible facilities, and increase greenery. Communities should also enhance social environments by improving healthcare services, ensuring accessible medical care, and organizing cultural and recreational activities to promote older adults’ social participation and improve their QoL.